Ser Mexicano o Húngaro? el problema de la identidad en la narrativa de Susana Wein - Csikós, Zsuzsanna (Acta Hispanica, 2008)
The oeuvre of Susana Wein, Mexican writer of Hungarian origins often represents the controversial quest for identity carried out by immigrants and their descendants. The author proposes to examine these dilemmas of identity in Wein’s collection of short stories En tiempo mexicano... cuentos húngaros (1985) and her novel titled La abuela me encargó a sus muertos (2005), both written in Spanish. The characters of Wein’s prose enable the reader to follow the evolution and change of the problematics of identity from one generation to the next. For example, while the female protagonist of the short story Draga Rocza is proud of her Hungarian identity and is determined to preserve it, the heroine of Una historia de amor has ambitions of quick assimilation, motivated by social and individual interests. The narrator figure of the short story El día en que renuncié a mi nacionalidad presents the dilemma of second-generation immigrants born into a different culture. The author argues that the characters of Wein’s novel undergo the same identity crisis: the grandmother’s homesickness never seems to cease, the grandchild wants to return to her roots, and Uncle Isidor symbolizes the importance of remembering. Thus, Wein’s prose offers a fusion of history and literature, filling the dry historical facts with life through her characters.